If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8 = -32 Reorder the terms: -8 + 3x = -32 Solving -8 + 3x = -32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 3x = -32 + 8 Combine like terms: -8 + 8 = 0 0 + 3x = -32 + 8 3x = -32 + 8 Combine like terms: -32 + 8 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| 7v^2+4=-29v | | 1x-5x^2=0 | | -9+-8= | | 1.4q-3.1-4.7q=4.3q-4.7 | | 5(x+9)+4=-6(x-9)-7 | | b^2-4b=02 | | -8=3t+6 | | 14x-4(9x-40)=355 | | m^2=45 | | 5p-24=-28+3p | | y=-0.8x+6 | | x-2+2=1 | | m^2+20m-85=-4 | | 20-x=19-2x | | 2m-5=20-3m | | x=-6+2x^2 | | 10-(-4r)=30 | | 2n^2+9n=-4 | | 4x+6=-58 | | -24+12=m-2 | | x+2=4x(x-3) | | 90+2x=180 | | 2m-(4m+12)=6 | | 5-5y+y-1=-23 | | 3.8=m+1.7 | | 2(x-1)+6=-3(x+8) | | -.4n=3.2 | | -49+-r=-76 | | p-6=-14 | | -10=-12+.57n | | x^2+23+10x-6=136 | | 75+35h=180 |